Performance assessment of elite coconut genotypes and hybrids for economic and quality traits and oil yield: Performance assessment of elite coconut genotypes and hybrids for economic and quality traits and oil yield - S PRANEETHA; SIVAKUMAR; L PUGALENDHI; P IRENE VETHAMONI (Journal of Oilseeds Research, 2023)
Coconut (Cocos nucifera L.) is an important plantation crop of the tropics cultivated in more than 80 countries across the globe. Coconut is a monotypic species with two different botanical forms namely tall and dwarf types. India owns a leading position in the world in coconut production and productivity. Coconut is cultivated in an area of 2082.11 thousand ha in more than 16 states of the country producing 23904.10 million nuts with an average productivity of 11481 nuts/ha. The four southern states of India, accounting for more than 92 per cent of the total coconut production in the country include Kerala, Tamil Nadu, Karnataka and Andhra Pradesh (Coconut Development Board, 2018). The major source of coconut production comes from the tall coconut varieties, while dwarf and hybrid varieties meant especially for tender coconut cultivation contribute for about 10 per cent of the total production.